APLIKASI PEMBELAJARAN SUARA HEWAN BAGI ANAK USIA 3-5 TAHUN BERBASIS ANDROID (Information Technology and Telematics, 2014)
AbstrakThe development of increasingly advanced technology applications with increasing applications using the Android operating system can facilitate in every way . Applications for early childhood learning is still relatively small . Currently dominated by applications that cater to adults . With this application can help in learning to early childhood ( earlychildhood) . Therefore this application can help improve a child's interest in introducing voice applications on the application of excess animals with an attractive appearance design and the pictures and sounds that can make children more interested .The subject of this study is to make animal sounds learning applications . The data used is a genius - type animal sounds such as birds , mammals and reptiles as many as 16 images to be created with minimal android 2.2 froyo operating system version .The objectives to be achieved is to build an application and are expected to be useful for the user / user . The results in this study is the application of learning animal sounds for children aged 3-5 years can be used sabagai android -based  educational materials for introducing the sound of animals and help train the hearing properly to the child .Keyword : Animal Sounds Application, Mobile, Android